Welfare implications of closed-cycle farming of Atlantic bluefin tuna (Thunnus thynnus) - Meyer, Bevin; Emam, Wasseem (Frontiers in Animal Science, 2024)
There is an increased demand for tuna meat to supply the growing global sushi and sashimi market. Current methods to farm tunas, especially Atlan3c Bluefin Tuna (ABFT; Thunnus thynnus), are unsustainable. This is driving a movement towards closed-cycle ABFT aquaculture, i.e., farming tuna from spawning and hatching to slaughter on land, to try and meet the demand for these fish. Tunas are not domes3cated species and thus face different challenges in terms of closed-cycle aquaculture when compared to other farmed fish species. Tunas also possess unique physiological traits such as regional endothermy and ram ven3la3on which affect their needs and how they are farmed. No current global standards exist to measure or monitor ABFT welfare in cap3vity, because there are many unknown factors surrounding ABFT welfare in intensive aquaculture se]ngs. There is a need to conduct studies which measure the baseline physiological parameters of ABFT in closed-cycle systems. Issues such as manipula3on of breeding cycles, tank design, and slaughter procedures need a_en3on and further research before such welfare indicators can be established. Stress is an overarching concern for animal welfare. In par3cular, pre-slaughter crowding and stress nega3vely affects the quality of the meat produced due to lac3c acid build up in the red muscle. Further research needs to be conducted throughout all life stages in terms of both animal welfare implica3ons and commercial viability of intensively farmed ABFT.